46 XX Congenital Adrenal Hyperplasia (CAH) after Clitoroplasty, Labioplasty, and Vaginoplasty - Rahmat Husein; Besut Daryanto; Paksi Satyagraha; Pradana Nurhadi (Jurnal Kedokteran Brawijaya, 2022)
Congenital adrenal hyperplasia (CAH) is the most common cause (60%) of Disorder of Sex Development (DSD), which causes three problems: symptoms and conditions arising due to adrenal endocrine disorders, long-term treatment, and quality of life due to genital ambiguity. An 18-year-old female patient was diagnosed with simple virilizing CAH and had genital ambiguity from birth. The patient was raised as a male. Overall, the examination results indicated a female. Physical examination before surgery showed virilization, such as external genital pigmentation, precocious pubic hair, and bilateral impalpable testis. The karyotype genetic examination confirmed female: 46, XX. Eventually, the patient decided as a female and underwent surgical management consisting of clitoroplasty, labioplasty, and vaginoplasty, followed by long-term corticosteroid therapy. Observations were made for three years after surgery to see the progress of the patient's condition. After undergoing glucocorticoid therapy and surgery, the patient had not experienced menstruation. Her breasts did not enlarge, and mustache and beard were still growing on her face. The patient was concerned about her condition, especially about the risk of infertility and inappropriate physical changes. The management of virilization in CAH with genital ambiguity should be seen from psychological and surgical perspectives. Understanding the disease, the goals of surgery, long-term treatment, and social adaptation help improve quality of life and reduce negative stigma.